Bridging the Gap in Real Estate Education: Higher-order Learning and Industry Incorporation. Issue 1 (1st July 2018) - Palm, Peter; Pauli, Karin Staffansson
Abstract: We outline how the industry can take an active part in an undergraduate course of real estate management to enhance student learning and break through the learning barrier. While it is beneficial to include industry-based guest lecturers, there are associated challenges for the teacher to uphold academic standards. These lectures provide the students with a live case to enhance the learning process. They inspire students to push themselves and are a natural way to break the learning barrier and develop higher-order learning.